Mental health needs and coping resources of participants in a prostitution pre-sentencing court program. Issue 8 (16th November 2020) - Schultz, Tammy; Canning, Sally Schwer; Estabrook, Hannah; Wong, Priscilla
Abstract: There is an expanding number of prostitution problem-solving courts; however, empirical findings regarding the mental health needs of participants in these specialty courts are sparse. This study examines the mental health needs and coping resources of 33 participants in a prostitution pre-sentencing program. Levels of trauma exposure, posttraumatic stress, posttraumatic growth, and religious coping were compared to 60 participants in a prostitution problem-solving court. Both groups endorsed extensive trauma exposure and posttraumatic stress. Still, the pre-sentencing participant's levels of posttraumatic growth and religious coping were substantial. Despite no group differences in trauma exposure or religious coping, pre-sentencing participants' levels of posttraumatic stress were significantly higher and their posttraumatic growth significantly lower, than the problem-solving court participants. Moderation analysis showed the relation between posttraumatic stress and posttraumatic growth varied depending on whether participants were in the pre-sentencing or problem-solving court. Posttraumatic stress inversely predicted posttraumatic growth for pre-sentencing participants but not for problem-solving court counterparts. The divergence in the relationship between variables was greatest for participants with the highest posttraumatic stress. Research-guided assessments of mental health needs and coping resources can inform the recruitment of participants and the development and implementation of these programs.